Hoof Overgrowth in Saanen Goats: A Study on Relationship Between Hoof Overgrowth, White Line Disease, Lameness and Body Condition - Bozkan, Z; Bilgen, Z; Bulut, O; Kibar Kurt, B; Gülendağ, E; Belge, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Hoof diseases are very common causes of lameness and hoof health, is very important factor for productivity and yield capacity in the small ruminants. This study was conducted in 97 Saanen goats aged 12-18 months, and weighing between 30-40 kg. Hoof overgrowth (HO), white line disease (WLD), lameness score (LS) and body condition score (BCS) were scored by using 3-point, 5-point, 4-point and 5-point scale systems respectively. The hooves of all goats were evaluated in terms of foot rot and interdigital dermatitis, toe granuloma/abscess and laminitis as absent or present and were not found in any of the goats included in the study. A negative and significant relationships were found between the BCS and LS, HO and WLD scores. Mean HO was significantly lower only for the right fore claw, but there was statistically significant difference between all four claws for WLD. Also, positive and highly significant relationship was found between HO and WLD. The incidence of HO between the fore and hind claws was no significantly different, but WLD in the hind claw was significantly higher than the fore claws. Consequently, in goats, lower BCS was associated with increase in the severity of LS, HO and WLD. Also, at a higher rate WLD was seen in the hind legs and, it has been demonstrated that HO may predispose to WLD.